PERBANDINGAN EFEKTIVITAS HAND SANITIZER DENGAN TISU BASAH TERHADAP PERTUMBUHAN Staphylococcus aureus - Tia Humaira Zahrah; Almatin Puspa Dewi; Wulan Fitriani Safari (YCMM, 2021)
Infectious diseases are diseases caused by pathogenic microorganisms and are very strong. One of the pathogenic microorganisms is Staphylococcus aureus. Organisms as living things certainly need to get them by reproducing in other supplies by moving or spreading. Components of transmission of pathogenic organisms to defenseless hosts should be alternately possible, including direct and indirect means. The purpose of this study was to determine whether there was a comparison of the effectiveness of hand sanitizers with wet wipes on the growth of S. aureus. This research is an experimental study with a cross sectional research design. The sample amounted to 13 using purposive sampling technique. Data were collected through observation at the Health Analyst Vocational School of the Directorate of Health. The data was processed using statistical software with the Independent T-test. The largest diameter for hand sanitizer is 12.67 mm and the largest diameter for wet wipes is 19.92 mm. The results of the analysis showed that there was a comparison of the effectiveness of hand sanitizer with wet wipes on the growth of s. aureus.